2022
DOI: 10.1177/0271678x221135658
|View full text |Cite
|
Sign up to set email alerts
|

Retinal capillary microvessel morphology changes are associated with vascular damage and dysfunction in cerebral small vessel disease

Abstract: Cerebral small vessel disease (SVD) is a cause of stroke and dementia. Retinal capillary microvessels revealed by optical coherence tomography angiography (OCTA) are developmentally related to brain microvessels. We quantified retinal vessel density (VD) and branching complexity, investigating relationships with SVD lesions, white matter integrity on diffusion tensor imaging (DTI) and cerebrovascular reactivity (CVR) to CO2 in patients with minor stroke. We enrolled 123 patients (mean age 68.1 ± SD 9.9 years),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…They showed that their technique can work as a generalized approach for retinal morphology analyses. Of note, such hybrid models can be impactful, since retinal imaging is not only used to assess ophthalmic pathologies, but also changes in retinal morphologies that may occur early in a broad spectrum of diseases, such as Alzheimer's [154], cardiac pathologies [155], cerebral small vessel disease [156] and others. Wang et al have proposed the MsTGANet, a UNet model enhanced with a Transformer block that consists of a series of multi-head self-attention mechanisms incorporated in the encoder, to capture both local and global pixel interactions early in the learning process [45].…”
Section: Segmentationmentioning
confidence: 99%
“…They showed that their technique can work as a generalized approach for retinal morphology analyses. Of note, such hybrid models can be impactful, since retinal imaging is not only used to assess ophthalmic pathologies, but also changes in retinal morphologies that may occur early in a broad spectrum of diseases, such as Alzheimer's [154], cardiac pathologies [155], cerebral small vessel disease [156] and others. Wang et al have proposed the MsTGANet, a UNet model enhanced with a Transformer block that consists of a series of multi-head self-attention mechanisms incorporated in the encoder, to capture both local and global pixel interactions early in the learning process [45].…”
Section: Segmentationmentioning
confidence: 99%
“…The corresponding vasculature lacks the hierarchical structure of the native vessels. The hierarchical structure of native vessels could reduce energy dissipation and reach maximum efficiency of energy use when transporting blood 129,130 . Therefore, it is crucial to build hierarchical vasculature within tissue engineering scaffolds.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…However, despite abundant literature on this subject, these is insufficient explanation regarding the biological processes of CSVD. Therefore, identifying novel biomarkers for a better understanding of CSVD may provide a strong foundation for advances in knowledge and clinical management 8,9 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, identifying novel biomarkers for a better understanding of CSVD may provide a strong foundation for advances in knowledge and clinical management. 8,9 Heart rate variability (HRV), as an index reflecting the balance of the autonomic nervous system (ANS), is related to prognosis of cardiovascular disease. 10 Moreover, lower HRV is associated with hypertension, diabetes, cognition, emotion, and sleep disorder.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation